Examining The Corporate Social Responsibility Disclosure Among LQ45 Index Companies - Hapsari, Dini Wahjoe; Novita, Fahra (UNIVERSITAS PAKUAN, 2023)
Concern for society as a consequence of a company's operations is known as Corporate Social Responsibility (CSR). This research examined the effect of the independent board of commissioners, gender diversity, and educational diversity on CSR disclosure carried out in companies in the non-financial LQ45 index listed on the Indonesia Stock Exchange (IDX). Sample selection using purposive sampling, a total sample of 54 companies from 2019 to 2021. The analysis technique uses a panel data regression model. The results showed that the independent board of commissioners affects CSR disclosure. While gender diversity and educational diversity does not affect CSR disclosure. The independent board of commissioners has carried out its function to supervise and control so that corporate governance runs well. Certainly, this will increase the company's CSR disclosure.